Pengaruh Berpikir Induktif Dalam Pembelajaran Getaran dan Gelombang Dikelas VIII SMPN Bosar Galugur Kecamatan Tanah Jawa - Surbakti, Mariana; Nainggolan, Irawati Kristin M.; Sitorus, Parlindungan (LPPM Universitas HKBP Nommensen, 2022)
This research aims to find out the influence of inductive thinking learning models in physics learning on Vibration and Wave Material of Grade VIII in SMPN Bosar Galugur Village, Tanah Jawa Sub-District. This type of research is a